THE EFFECT OF THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON THE PROBLEM-SOLVING ABILITY OF THE HUMAN RESPIRATORY SYSTEM MATERIAL IN STUDENTS OF SMA NEGERI 1 BAHOROK: PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN ‎PEMECAHAN MASALAH MATERI SISTEM PERNAPASAN MANUSIA PADA SISWA SMA NEGERI 1 ‎BAHOROK - Milda Aulya; Kartika Manalu (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students' ‎problem-solving abilities in the topic of the human respiratory system at SMA Negeri 1 Bahorok. ‎The research employed a quantitative approach using a quasi-experimental design with a ‎pretest-posttest control group design. The sample consisted of 60 11th-grade science students ‎divided into two groups: an experimental class (using PBL) and a control class (using ‎conventional learning). The instrument used was an essay test consisting of 10 questions. The ‎results showed a significant difference between the posttest scores of the experimental and ‎control classes. The average posttest score of the experimental class was 95.00, while the ‎control class scored 63.33. The Independent Samples t-Test indicated a significance value of ‎‎0.000 (< 0.05), confirming that the PBL model significantly influenced the improvement of ‎students' problem-solving abilities. Therefore, the PBL model is effective in enhancing students' ‎problem-solving skills, particularly in biology lessons on the respiratory system.‎